Ownership of change: Participatory development of a novel latent construct for neighborhoods and health equity research. (September 2022) - Binet, Andrew; Nidam, Yael; Houston-Read, Rebecca; Lopez, César Garcia; del Rio, Gabriela Zayas; Abreu, Dina; Baty, Carl; Baty, Arnetta; Genty, Josee; Graham, Goldean; Joseph, Jeff; Justice, Will; et al.
Abstract: Processes of neighborhood change are important determinants of health. One salient dimension of the experience of neighborhood changes is a person's evolving sense of empowerment over the changes around them, such as development of new housing or shifts in economic opportunity. Community residents collaborating on a Participatory Action Research study developed the novel construct "ownership of change" to capture this psychosocial process, and hypothesized that it may help explain the relationship between neighborhood change and health. In this paper, we describe our participatory process for developing a way to measure ownership of change, explore the construct's validity, test the hypothesis that it is associated with health, and analyze qualitative data to understand the process through which one's sense of ownership of change is produced. We argue that the construct is useful for studying the role of neighborhood changes in shaping health, and that building ownership over neighborhood change must be a key dimension of urban planning and policy for health equity. Highlights: The construct "ownership of change" was developed via Participatory Action Research. Ownership of change captures empowerment over meso-level place-based changes. Ownership of change is positively associated with health. The structural conditions of racial capitalism influence ownership of change. Ownership of change is key for achieving health equity in cities.